Analisis Peran IMF terhadap Fenomena Inflasi tahun 1997-1998 di Negara Thailand - Aziza, Aliya Nur; Fathana, Audita; Yulianto, Ayun Faiza (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2019)
Monetary crisis in Asia is a condition when the huge inflation takes place in almost all of the Southeast Asia countries. Thailand become pioneer of monetary crisis in Asia. The value of the country's currency in Thailand fell due to the government decision in adopting managed-float exchange policy of Baht currency to the Dollar America. This led the government to take the decision for seeking a help from IMF in order to recover their economic stability. However, this attempt became more complicated as a consequence of IMF regulation. IMF could not provide a solution to recover economic crisis as some of the parties disagree with the financial support by providing loan for Asia countries. The inflation also was one of the reasons behind of IMF incapability to provide solutions tackling this issue. Therefore, this paper has the aim to investigate the role of IMF towards the inflation issue in Thailand in 1997-1998. The method used to collect data is to use Internet based research with data analysis techniques using qualitative descriptive methods. The results of this study are that the IMF issued several policies including Monetary Tightening Policy, Fiscal Austerity, and Application of Letter of Intent.